A 10 Gbps differential low-power loss of signal detector for AC-coupled serial transceivers in 28 nm CMOS technology. (October 2016) - Kawar, Sanad; Abugharbieh, Khaldoon; Al-Akel, Waseem; Mohammed, Mahmood
Abstract: This work presents a differential low-power 10 Gbps loss of signal (LOS) detector for high-speed AC-coupled serial transceivers. The detector is designed in 28 nm CMOS technology. It includes a novel comparator circuit that compares a differential input signal to a differential reference voltage with minimal sensitivity to the common mode voltage of the input signal. The LOS detector is capable of properly detecting a valid signal that has an external eye opening as low as 85 mV and an internal eye opening as low as 36 mV at the input pads. It asserts LOS if the external eye opening is below 50 mV. It consumes 113uW from a 0.9 V nominal power supply at 10 Gbps date rate and properly asserts an LOS state in 25.5 nS at typical corner operation. It occupies 0.00169 mm 2 of area. In simulations that include metal parasitic resistance and capacitance, the detector is shown to withstand process, voltage and temperature (PVT) variations and satisfy the commercial operating temperature range. The design and layout of the system were implemented in Synopsys Custom Designer using 28 nm CMOS device models.